The boundary element method for elasticity problems with concentrated loads based on displacement singular elements - Yuntian Feng (Engineering Analysis with Boundary Elements, 2019)
The boundary element method (BEM) has been implemented in elasticity problems very successfully because of its high accuracy. However, there are very few investigations about BEM with concentrated loads. The displacement at the concentrated load point is infinite and traditional elements will lead inaccurate results near the concentrated load point. This paper proposes two types of displacement singular elements to approximate the displacement near concentrated load point, and high accuracy can be obtained without refinement. The second type of displacement singular element is a general element type, which can work well for both problems with or without boundary concentrated loads. Numerical examples have been studied and compared with results obtained by traditional BEM and finite element method (FEM) to show the necessary of the proposed methods.